2014
DOI: 10.1016/j.rmed.2014.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of asthma in sub Saharan Africa: A cross sectional community survey in a suburban Nigerian town

Abstract: The prevalence of asthma in this suburban Nigerian population is low. Determinants of adult asthma distribution in low-income setting need further clarification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…This present study also demonstrates a high prevalence of allergic rhinitis (22.8%) comparable to previous reports in Nigeria and other parts of the world (9%-29.6%) [14,46–47]. We also substantiate a significant association between the co-existence (70–80%) of allergic rhinitis with asthma and the increased risk of asthma among persons with allergic rhinitis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This present study also demonstrates a high prevalence of allergic rhinitis (22.8%) comparable to previous reports in Nigeria and other parts of the world (9%-29.6%) [14,46–47]. We also substantiate a significant association between the co-existence (70–80%) of allergic rhinitis with asthma and the increased risk of asthma among persons with allergic rhinitis.…”
Section: Discussionsupporting
confidence: 91%
“…The low prevalence of physician diagnosed asthma among adults (4%) in this study is similar to the prevalence in many African countries, but lower than that in most Western European countries such as Australia and Sweden (20%) [27]. The lower prevalence of physician diagnosed asthma compared to clinical asthma in most African countries is likely to relate to limitations in access to health care services as we previously alluded to [1314,3132]. In Nigeria, low universal health coverage [33] particularly when put into the context of the very low earning ($100 monthly) by most households is an important constraint to accessing healthcare [34].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The general characteristics (age, gender, residence) of the respondents were almost similar to those described by Pefura-Yone in Cameroon [19] and Obaseki in Nigeria [32]. The young age may be explained by the early onset of asthma, which is the most common chronic disease affecting children [33].…”
Section: Discussionmentioning
confidence: 75%
“…Previously published studies evaluating the prevalence of BA have demonstrated that BA prevalence varies across different countries/populations [ 5 21 ]., Although the prevalence of BA has been estimated in CIS and post-soviet countries (e.g. Russia) as a part of global surveys or in separate studies, there is lack of large epidemiologic analyses of BA prevalence in the Commonwealth of Independent States (CIS) area.…”
Section: Introductionmentioning
confidence: 99%